The collected writings of John Maynard Keynes, Volume 14, The general theory and after - Keynes, John Maynard 1883-1946 (Cambridge University Press for the Royal Economic Society, 2013)
This volume, with its companion, Volume 13, provides all the surviving letters, drafts and articles arising from Keynes's work as a monetary economist between 1924 and 1939. It contains wherever possible both sides of all correspondence concerning his Treatise on Money and General Theory, both before and after publication, as well as complete texts of all surviving drafts of both works. In addition it contains important correspondence concerning D. H. Robertson's Banking Policy and the Price Level and such post-General Theory contributors as R. F. Harrod's first work on the theory of economic growth. As such, it provides a remarkable chronicle of one man's intellectual development over the quarter of a century that saw a revolution in economics
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Keynes, John Maynard / 1883-1946 / General theory of employment, interest, and money; Keynes, John Maynard / 1883-1946 / Correspondence; Keynesian economics; Monetary policy